PENGARUH FAKTOR KEUANGAN DAN UKURAN PERUSAHAAN PADA DIVIDEND PAYOUT RATIO PERUSAHAAN PERBANKAN - Mahaputra, Gede Agus; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 9 No 3 (2014), 2014)
The purpose of this study was to determine the effect of profitability, leverage, liquidity, cash position, and the size of the company on the dividend payout ratio of banking companies in Indonesia Stock Exchange. This study used quantitative research is to use the financial statements of banking companies in Indonesia Stock Exchange during the period 2008-2012 and found 32 companies, while only 9 companies that qualify. It was found that the positive effect on the profitability of the dividend payout ratio. Leverage also has a positive effect on the dividend payout ratio. However, the negative effect of liquidity on dividend payout ratio. Meanwhile, the cash position has no effect on the dividend payout ratio and so does not affect the size of the company's dividend payout ratio.
Keywords: Dividend Payout Ratio